Bookstack for Teaching Materials & Practical Guidelines as Wikisource for Politala - Fitriyani, Yuli; Aristi, Nina Mia; Zulfahri, Aidil Fajar; Herpendi; Hafizd, Khairul Anwar; Fathurrahmani; Ridha, M. Najamudin (Cattleya Darmaya Fortuna, 2024)
In 2023, Tanah Laut State Polytechnic (Politala) will be 14 years old since its founding. Various prestigious achievements have been achieved, including the most recent in 2021, where Politala received the best SAKIP award among all Polytechnics in Indonesia. This achievement cannot be separated from the good management of higher education by the leaders. Facing the challenges of rapidly developing digitalization, Politala continues to strive to adapt to the needs to support its vision, namely